The technical challenges of cloud computing and their effects on usage - Baktır, Ahmet Cihat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
Cloud computing is a computer technology that enable convenient, on demand and pay-as-you-go access to a pool of shared resources. Recently, cloud computing is taken into consideration by the companies that operate in many different sectors. It has an important role in the competition between the companies as it grows and increases the efficiency of companies by providing advantages more than in-house system. However, number of researches and studies about cloud computing is relatively less in Turkey than other countries. A considerable amount of companies are still not eager to adopt the cloud computing because besides advantages it provides, there are also several crucial challenges that are seen as a barrier to use cloud computing. The aim of this study is analyzing the technical challenges of cloud computing and their effects on usage in companies that operate in Turkey. The technical challenges that are analyzed in this study are gathered and classified by studying the related researches. The analysis results examine that whether Information Technology (IT) personnel in Turkey are aware of these challenges and these challenges affect the usage of cloud computing within their organization. According to the findings, the challenges about cloud applications and cloud migration negatively affect the usage of cloud computing while the challenges about privacy and security, account control, cloud structure, virtualization, monitoring, Internet connection and SLA do not affect the usage of cloud computing in negative way.
Keywords: Cloud computing.; Cloud computing -- Security measures.